2021
DOI: 10.2151/sola.2021-035
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analyses on the Seasonal Rainfall Trend and Annual Rainfall Variability in Bhutan

Abstract: This is a PDF of a manuscript that has been peer-reviewed and accepted for publication. As the article has not yet been formatted, copy edited or proofread, the final published version may be different from the early online release.This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Previous studies on rainfall trends in Bhutan revealed a general decreasing trend, but future projections show an increase with a substantial change in the spatial pattern of winter and summer monsoon precipitation [1,26,30]. Sharma et al [31] revealed that rainfall patterns in the south of the country are negatively influenced by the El Nino-Southern Oscillation (ENSO) cycle, while the majority of the country remains unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on rainfall trends in Bhutan revealed a general decreasing trend, but future projections show an increase with a substantial change in the spatial pattern of winter and summer monsoon precipitation [1,26,30]. Sharma et al [31] revealed that rainfall patterns in the south of the country are negatively influenced by the El Nino-Southern Oscillation (ENSO) cycle, while the majority of the country remains unaffected.…”
Section: Introductionmentioning
confidence: 99%